Association of Plasma 7-Ketocholesterol With Cardiovascular Outcomes and Total Mortality in Patients With Coronary Artery Disease. Issue 10 (12th May 2017) - Song, Jiayi; Wang, Duan; Chen, Hongen; Huang, Xiuwei; Zhong, Yuan; Jiang, Nan; Chen, Chaogang; Xia, Min
Abstract : Rationale: : 7-Ketocholesterol (7-KC), a form of cholesterol oxidation product, plays an essential role in the atherogenesis in animal models. Objective: : We sought to determine the association of circulating 7-KC with clinical cardiovascular outcomes and total mortality in patients with stable coronary artery disease. Methods and Results: : We measured the plasma 7-KC levels by high-performance liquid chromatography in a prospective cohort study of 1016 patients (mean age, 63.2 years; male 61.1%) with stable coronary artery disease who were recruited from December 2008 to December 2011 and followed up for a median of 4.6 years. We adjudicated myocardial infarction, hospitalization of heart failure, cardiovascular death, all-cause death, and composite end points of myocardial infarction/heart failure/death by review of medical records and death certificates. We used multivariable Cox proportional hazards analysis to compare the incidence rate of cardiovascular events and all-cause death according to the quartile of the plasma 7-KC. During the median 4.6 years follow-up, totally 221 participants (21.8%) experienced a cardiovascular event or death. The adjusted risk of the composite end points was higher in the highest 7-KC quartile than in the lowest quartile (hazard ratio, 1.76; 95% confidence interval, 1.42–2.21; P <0.001). After adjustment for demographic and clinical variables and other biomarkers, including high-sensitivity C-reactive protein and NT-proBNP (N-terminal pro-B-type natriuretic peptide), 1 SD increase in the 7-KC level remained associated with a 36% higher rate of composite outcomes (hazard ratio, 1.36; 95% confidence interval, 1.22–1.48; P =0.007). Plasma 7-KC clearly improved various model performance measures, including C statistics, integrated discrimination, and category-free net reclassification. Conclusions: : High 7-KC levels are associated with increased risk of cardiovascular events, total death, and composite outcomes in patients with stable coronary artery disease. Abstract : Supplemental Digital Content is available in the text.